Access to justice for the urban poor toward inclusive cities. (Asian Development Bank, 2010)
This publication suggests solutions that can be built into the design of urban development projects undertaken by the Asian Development Bank (ADB) to address the common problems and grievances of the urban poor, and improve urban governance overall. It also identifies successful or promising community based approaches to dispute resolution that can likewise be adopted in urban project design."--p.1